s Santun dalam Bermediasosial dikalangan Remaja perspektif Pandangan Islam - Khusnul Khotimah; Arifiyah Tsalatsati AM; Ali Fauzan; Hero Prayogo; Ouedraogo Saidoue (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Social media is a modern digital platform that can help users wherever they are. One of them is Tiktok. Tiktok is a visual and audio communication forum containing a variety of videos used by mostly millennial teenagers. How to use TikTok is similar to other social media: first create an account, then play by scrolling from the top to the bottom of the screen, and the current information will be displayed as a video. Tiktok has many fans, especially teenagers. The rise of this application may cause a change in the values of civility in social media. Because a significant number of teenagers watch parody videos that they watch in order to answer questions from their parents or elders. This study is about: 1) How can teenagers be polite when using social media? 2) Polite usage of social media from an Islamic perspective. The purpose of this study is to 1) practice civility in social media use among teenagers and 2) demonstrate the importance of civility in social media use from an Islamic perspective. The type of study is qualitative and based on a field research approach. The purpose of field research is to uncover the meaning and actual behavior of the surrounding community. Field research methods are used when survey or experimental methods are considered impractical or when the research area is still very broad. Based on the research objectives and using the methods and techniques of this field, it is carried out using various suitable methods and approaches. The results and discussion of the study are as follows. 1) A young person may spend 2 to 8 hours a day using social media to influence language. It's polite if it doesn't sound pushy or arrogant, gives the person a choice, and makes the person feel at ease. 2) The concept of politeness in language based on Al-Quran and Hadith, i.e. Qs. In Tawbah verse 114, Qs. Hud verse 87, Qs. Ali Imran verse 155 and Qs. al-Hajj verse 59. Verses 1 and 2 state that two prophets were patrons: Prophet Ibrahim and Prophet Shuaib. On the other hand, verses 3 and 4 say that Allah is Forgiving.